Classical Ehlers-Danlos syndrome: clinical, Histological and ultrastructural aspects Síndrome de Ehlers-Danlos clássica: aspectos clínicos, histológicos e ultraestruturais - Eduardo de Barros Coelho Bicca; Fabiano Bonow de Almeida; Giselle Martins Pinto; Luis Antônio Suíta de Castro; Hiram Larangeira de Almeida Jr (Sociedade Brasileira de Dermatologia, 2011)
A 12-year-old boy with difficulty in wound healing and scars of unusual appearance was examined. Thin, shiny and protruding skin, characterizing pseudotumoral lesions, was observed on his knees and elbows. Loose joints and increased skin elasticity were also observed. Light microscopy showed rare collagen bundles and loosely dispersed collagen fibers. Irregularly distributed elastic tissue was observed, and transmission electron microscopy revealed disorganized collagen fibers. In cross sections under high magnifications, fibers of varying diameters could be seen, as well as an irregular fiber outline. Scanning electron microscopy of the dermis showed disorganized collagen fibers, which were rarely arranged in bundles. Isolated and crossed-over fibers were also found Paciente masculino de 12 anos relatou dificuldade em cicatrizar, seguido por cicatrizes de aspecto infrequente . A pele dos joelhos e cotovelos é fina, brilhante e protrusa, caracterizando pseudo- tumores. Além disso apresenta hiperelasticidade cutânea e articular. A microscopia óptica demonstrou raros feixes colágenos, as fibras colágenas encontram-se dispersas. O tecido elástico está presente e secundariamente irregular. A microscopia eletrônica de transmissão também observou fibras colágenas desorganizadas e com cortes transversais em grande aumento evidenciou diâmetros variados e contorno irregular das mesmas. A microscopia eletrônica de varredura da derme demonstrou raros feixes colágenos e fibras colágenas isoladas e entrecruzadas